PENGARUH STRATEGI KNOW-WANT TO KNOW-LEARNED (KWL) TERHADAP PENGUASAAN KONSEP SISWA PADA MATERI EKOSISTEM - Nia Kurniasih; Milla Listiawati (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2018)
The purpose of this study was to determine the effect of KWL strategy on students' mastery of the material concept of ecosystems. The hypothesis of this study is the use of learning strategies KWL on ecosystem material and significant positive effect on students' mastery of concepts.The method used was a quasi experimental design with control group design nonequivalen. In this study, the population was seventh grade students of SMP Negeri 1 Cileunyi. Samples were taken with a purposive sample, take two classes, namely the class as a class VII-A and VII-F experiment as a control class. Data collection techniques derived from the test (multiple choice) by 20 questions, and nontes (questionnaire and observation sheet). Data processing is done by t test analysis.Mastery of concepts students are learning to use 74.02 KWL strategy with good category, while in the class without using the KWL strategy 64.51 with enough categories. The results of the posttest t test at significance level of 0.05% obtained tcount 11.73> 1.67 ttable so Ho is rejected and Ha accepted. The response of students who use the KWL strategy 80.40 with a very strong category, whereas the class without using 74.41 KWL strategy with strong category. Feasibility study of teachers who use the KWL strategy 96.66% and 90.00% of students with a very strong category, while the teacher without using KWL strategy 96.00% and 80.00% of students with a very strong category. Based on the results of this study concluded that the strategy of Know-Want to know-Learned (KWL) and a significant positive effect on students' mastery of the material concept of ecosystems.